Systems change: from theory to practice - Kessler, J J; Molenaar, J W (Aid Environment, 2022)
In recent years concepts such as market or sector transformation and s ystems change have become part of the mainstream development discourse . The aim is to address root causes that undermine the performance of sectors (e.g. agriculture, mining or energy) in order to achieve long- term and widescale impact. It seems, however, that it is not always cl ear to everyone using these concepts what is meant with these concepts and how it differs from ‘business as usual.’ Adopting a systems chang e approach is often seen as an incremental change from ‘business as us ual,’ while in most cases it implies a much more fundamental shift to the ‘way of working.’ Moreover, even where systems change has been mor e or less clearly defined, it remains a challenge to actually achieve it and to monitor it. To provide practitioners with relevant input, th is paper provides an overview of relevant insights from literature and AidEnvironment’s own experience in conceptualizing, implementing and monitoring systems change. The insights have been brought together in a number of ‘systems change characteristics (‘what is it?’), and syste ms change principles (‘how to do it?’), with actionable details. These are meant to support organisations in understanding and implementing systems change.